Escherichia coli specific bacteriophage isolated from various water sources in Central Bogor, Bogor City as an alternative antibiotic - Wally, Arga Darmawan; Pribadi, Eko S.; Setyaningsih, Surachmi (Jurnal Biologi Udayana, 2021)
The Research isolated specific phages of Escherichia coli in various water sample in Bogor Tengah, Bogor City and stored them. The Research was conducted in Bogor City in March and April 2020. Phage enrichment was carried out twice as the gold standard method of isolating phages. The plaque test was carried out to confirm the presence of phages in the collected water samples examined using the filtrate obtained only from the phage enrichment method. E. coli isolated in all water samples and phage obtained one water sample, namely the meat dyeing of Pasar Merdeka, Bogor City. The phage concentration in the water sample was 9.1 x 10 8 PFU/ml. The phage concentration level was considered high enough that it has the potential to be used in the therapy of bacterial infections caused by E. coli .